Combined Bone Marrow and Kidney Transplantation for the Induction of Specific Tolerance - Chen, Yi-Bin (Adv Hematol, 2016)
The induction of specific tolerance, in order to avoid the detrimental effects of lifelong systemic immunosuppressive therapy after organ transplantation, has been considered the “Holy Grail” of transplantation. Experimentally, tolerance has been achieved through clonal deletion, through costimulatory blockade, through the induction or infusion of regulatory T-cells, and through the establishment of hematopoietic chimerism following donor bone marrow transplantation. The focus of this review is how tolerance has been achieved following combined bone marrow and kidney transplantation. Preclinical models of combined bone marrow and kidney transplantation have shown that tolerance can be achieved through either transient or sustained hematopoietic chimerism. Combined transplants for patients with multiple myeloma have shown that organ tolerance and prolonged disease remissions can be accomplished with such an approach. Similarly, multiple clinical strategies for achieving tolerance in patients without an underlying malignancy have been described, in the context of either transient or durable mixed chimerism or sustained full donor hematopoiesis. To expand the chimerism approach to deceased donor transplants, a delayed tolerance approach, which will involve organ transplantation with conventional immunosuppression followed months later by bone marrow transplantation, has been successful in a primate model. As combined bone marrow and organ transplantation become safer and increasingly successful, the achievement of specific tolerance may become more widely applicable.